An Athlele’s Rest as a Factor in Increasing his Preformance (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The relevance of the research topic is determined by the fact that today in Uzbekistan one of the most significant issues is the education of modern society in matters of sports, the formation of good health and the formation of interest in a healthy lifestyle and the need for leisure sports and physical education. Resolving these issues is a necessary condition for the security of the nation and the further development of Russian society.The article examines the role of physical culture and sports in the life of modern society. The positive role of physical activity on the functional state of the human body is noted. Sport as a prevention of deviant behavior in modern society.